Back to the future: a belated history of ‘new’ science in the Ottoman Empire - Duygu Yıldırım; James Poskett (BJHS Themes, 2024)
What happens when fragmentary and too much information is flowing across the world? This article sketches the emergence of one such informational flow through the ubiquitous concept of ‘new medicine’ in the seventeenth-century Ottoman Empire in a historiographical corrective. Rather than presenting it as a unified category, I argue that Ottoman physicians used ‘new’ as a loose, multivalent and discursive term whose potentiality lay in its malleability for future use. Ready to bear any contingent meaning at a certain point in the future, the ‘new’ became a strategic tool to cope with the uncertainties evoked by early modern globalization and local epistemic crisis. It also helped Ottoman scholars and physicians develop a tentative design for how much information, and of what sort, was just enough for the learned and laypeople to know during precarious times. I further discuss the fact that since the Ottoman motivation for the usage of the notion of the ‘new’ is without a decisive motive, it still haunts our historiographical debates about what was truly new about Ottoman science.